2017
DOI: 10.4025/actasciagron.v39i1.30638
|View full text |Cite
|
Sign up to set email alerts
|

<b>Older leaf tissues in younger plants are more susceptible to soybean rust

Abstract: ABSTRACT. The aim of this study was to clarify the relationship between soybean leaf/plant age and the susceptibility to infection by Phakopsora pachyrhizi. Two studies were conducted in the greenhouse during the 2009/2010 season using the BRS 232 cultivar. The experimental design for Study 1 was fully randomized in a 2 x 3 factorial arrangement (phenological stage x age of the 4th, 5th and 6th trifoliate at the time of inoculation), and in Study 2, the experimental design was fully randomized with five treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
1
3
0
3
Order By: Relevance
“…Most forecasting models use only environmental factors; these usually include hours of wetness and temperature, considering that the pathogen and host (the other vertices of the triangular disease), are always present (M. C. Alves, Pozza, Costa, Carvalho, & L. S. Alves, 2011). In addition, the models usually not consider factors such as leaf age and susceptibility (Xavier, Martins, Fantin, & Canteri, 2017) and plant nutrition (Gaspar et al, 2015). The present study demonstrated that the presence of inoculum (the pathogen vertex) exerts a great influence on epidemics during the season.…”
Section: Discussionmentioning
confidence: 83%
“…Most forecasting models use only environmental factors; these usually include hours of wetness and temperature, considering that the pathogen and host (the other vertices of the triangular disease), are always present (M. C. Alves, Pozza, Costa, Carvalho, & L. S. Alves, 2011). In addition, the models usually not consider factors such as leaf age and susceptibility (Xavier, Martins, Fantin, & Canteri, 2017) and plant nutrition (Gaspar et al, 2015). The present study demonstrated that the presence of inoculum (the pathogen vertex) exerts a great influence on epidemics during the season.…”
Section: Discussionmentioning
confidence: 83%
“…Reductions in the disease severity in soybean might be related to depletion of the availability of free water for the pathogen infection process. A significant reduction in LWD was evidenced as soybean plants entered into the reproductive phenological stage, considered the most susceptible phase for disease occurrence (Young et al, 2011;Xavier et al, 2017). During this phenological stage mean LWD decreased from 13.4 to 9.0 h, reaching an average of 6.5 h during the third 10-day period of January (Figure 2), making the environment less unfavorable to SBR occurrence.…”
Section: Figurementioning
confidence: 99%
“…Thus, throughout the crop growing season in Pedra Preta neither the weather conditions nor the host characteristics favored the SBR occurrence in soybean production fields. However, by the time wet environmental conditions prevailed again and remained in a favorable range for SBR occurrence, soybean plants were at the beginning of flowering stage, coinciding therefore with a period of a high susceptibility to the SBR infection, and as a result disease progress turned out to be favored in the field (Table 3) (Young et al, 2011;Xavier et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…Na América do Sul o primeiro registro data de 2001 em algumas regiões do Brasil e do Paraguai, de onde o patógeno se alastrou rapidamente para outras áreas circundantes. Em 2004 o patógeno foi reportado no sul do domínio continental dos Estados Unidos da América, e algum tempo mais tarde infectando campos de soja no norte desse mesmo país (GOELLNER et al, 2010;YORINORI et al, 2005). O fungo P. pachyrhizi é um parasita obrigatório capaz de produzir urediniósporos e teliósporos.…”
Section: Ferrugem-asiática Da Sojaunclassified
“…A ferrugem-asiática da soja causada por Phakopsora pachyrhizi Syd & P. Syd é a principal e mais severa doença da soja no Brasil (LANGENBACH et al, 2016;XAVIER et al, 2017). A ocorrência da doença é atrelada às condições favoráveis ao desenvolvimento do patógeno.…”
Section: Introductionunclassified